Field optimization method of a dual-axis atomic magnetometer based on frequency-response and dynamics. (29th March 2018) - Xing, Li; Quan, Wei; Fan, Wenfeng; Li, Rujie; Jiang, Liwei; Fang, Jiancheng
Abstract: The frequency-response and dynamics of a dual-axis spin-exchange-relaxation-free (SERF) atomic magnetometer are investigated by means of transfer function analysis. The frequency-response at different bias magnetic fields is tested to demonstrate the effect of the residual magnetic field. The resonance frequency of alkali atoms and magnetic linewidth can be obtained simultaneously through our theoretical model. The coefficient of determination of the fitting results is superior to 0.995 with 95% confidence bounds. Additionally, step responses are applied to analyze the dynamics of the control system and the effect of imperfections. Finally, a noise-limited magnetic field resolution of 15 f T H z − 1 has been achieved for our dual-axis SERF atomic magnetometer through magnetic field optimization.